2018
DOI: 10.12911/22998993/89716
|View full text |Cite
|
Sign up to set email alerts
|

Ashes from Sewage Sludge and Bottom Sediments as a Source of Bioavailable Phosphorus

Abstract: Phosphorus is an element necessary for the growth of plants. As phosphate rock gets depleted, it becomes an increasingly scarce resource. Therefore, it seems necessary to implement simple methods of cheap and effective phosphorus recovery from waste. The ashes of municipal sewage sludge and bottom sediments constitute particularly valuable sources of phosphorus. However, these materials usually carry significant amounts of pollutants, including heavy metals. Optimization of ash phosphorus sequential extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The Ash + N treatment tended to show values that rarely stood out in comparison to the treatments of inorganic or organic fertilization, which seems in accordance with its initial composition. In general, bottom ashes are fertilizing materials that can be valued for their content in nutrients such as P, K, Ca or Mg [20][21][22], but which can also present toxicity problems as they may contain high levels of heavy metals, such as Cd, Cr or Pb [23][24][25][26]. In this study, neither aspect deserves to be highlighted, perhaps reflecting, once again, its initial mineral composition and the moderate rates in which it was applied.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The Ash + N treatment tended to show values that rarely stood out in comparison to the treatments of inorganic or organic fertilization, which seems in accordance with its initial composition. In general, bottom ashes are fertilizing materials that can be valued for their content in nutrients such as P, K, Ca or Mg [20][21][22], but which can also present toxicity problems as they may contain high levels of heavy metals, such as Cd, Cr or Pb [23][24][25][26]. In this study, neither aspect deserves to be highlighted, perhaps reflecting, once again, its initial mineral composition and the moderate rates in which it was applied.…”
Section: Discussionmentioning
confidence: 88%
“…Fly and bottom ashes from burnt wood biomass in thermal power plants are materials of varied elemental composition, but with potential to be used in agriculture. These fertilizing materials can contain high levels of some valuable nutrients, such as calcium, phosphorus, potassium and/or magnesium [20][21][22], but also high levels of heavy metals [23][24][25][26] Nonetheless, several studies have shown benefits in soil properties or in the growth of agricultural and forestry plants through the application of wood ash [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…All technologies and solutions are focused on use of waste as an alternative source of raw materials (Ciesielczuk et al, 2018) in fertilizer industry should be evaluated from economic (Generowicz et al 2011, Kowalski et al 2012, Jóźwiakowski et al 2015, Makara et al 2016, environmental (Feng andReisner 2011, Koneczna andMoghim and Garna 2019) and social points of view. The impact of the above technologies on the environment can be evaluated using environmental assessment methods (Kowalski et al, 2007, Gaska et al, 2017.…”
Section: Introductionmentioning
confidence: 99%